Basal cell ameloblastoma–review of literature with report of three cases - Girish B Giraddi; AJ Sai Anusha (Journal of Oral Biology and Craniofacial Research)
ABSTRACT: The ameloblastoma is the most common epithelial odontogenic tumor of the jaw with several histologic variants viz. follicular, plexiform, acanthomatous, desmoplastic, and granular cell and basal cell types. The basal cell ameloblastoma is a rare histological variant which tends to demonstrate microscopic features similar to cutaneous basal cell carcinoma and basaloid squamous cell carcinoma. In the current article we report three cases and review the literature of this rare tumor